Literature Review: The effect of modification diet and antioxidant on inflammatory and oxidative stress concentration in obesity - Hanifah Mardhotillah; Diana Nur Afifah; Adriyan Pramono (AcTion: Aceh Nutrition Journal, 2024)
Obesity is also associated with increased inflammation and oxidative stress. Mediterranean and dash diets, as well as antioxidants, can reduce inflammation and oxidative stress levels in obesity. This study aimed to determine the effects of dietary modifications and antioxidants on inflammatory and oxidative stress levels in obesity. This study was carried out using the literature review method using PubMed, Science Direct, and Google Scholar databases with the keywords Mediterranean Diet, DASH Diet, Antioxidant, Obesity, Inflammation, and Oxidative Stress. The inclusion criteria in this literature are articles published in the last 5 years (2018-2023) using RCT, in English, subjects >18 years old with obesity, interventions providing Mediterranean and dash diet, antioxidants derived from natural ingredients, and articles that can be accessed online. Articles were selected individually through a double process, considering the three main research quality criteria. This study showed that a modified diet and antioxidants can reduce inflammatory biomarkers and oxidative stress in obesity by suppressing NF-κB signaling and protecting against DNA damage. In conclusion, a modified diet and antioxidants can reduce inflammatory and oxidative stress in obesity.